25S–18S rDNA IGS of Capsicum: molecular structure and comparison - Grabiele, Mauro; Debat, Humberto Julio; Moscone, Eduardo Alberto; Ducasse, Daniel Adrian (Springer, 2019)
The primary and secondary structures of the intergenic spacer (IGS) between the 3′-end of 25S ribosomal RNA (rRNA) gene and the 5′-end of 18S rRNA gene are described for the cultivated chili pepper Capsicum pubescens. The recognized functional IGS is 2,078 bp in length. According to nucleotide base composition, regulatory elements, and conserved and repeated sequences the IGS can be divided into seven structural regions (SRI–VII). SRI comprises three copies of GAGGTTTTT-like motif, a probable transcription termination site in Solanaceae. At 3′-end, there are 21 bp matching the 18S rDNA. SRII is formed by 47 repeats of CACCATGG-like motif, the shortest repetitive region found in plant rDNA to date. SRIII is highly AT-rich, preceding SRIV, a highly conserved region in Solanaceae containing the transcription initiation site (TIS) TATATAAGGGGGG. The external transcribed spacer (ETS) is 966 bp in length. SRV-VII, downstream of the TIS, possesses eight inverted repeats, and three predicted stem-loops show pre-micro RNA (miRNA)-like structural features. Intragenomic variation is presented, and data are compared with characterized Solanaceae 25S–18S rDNA IGS.